Taiping zoo and night safari navigation using mobile application / Siti Norasmawati Kadir - Siti Norasmawati, Kadir (2016)
This project is about developing the mobile application to assist visitors in searching animal and point of interest on an interactive map. This mobile application was choosing Android as the main platform because the ratings of user that use mobile phone in Android platform are rapidly increased. Taiping Zoo and Night Safari are selected as this project‟s case study. MapsAlive tools are chosen in order to implement an interactive map. The application provides information regarding animal in the zoo to visitors. Besides that, the application gives detail information about Taiping Zoo and Night Safari, entrance fees, visiting hours and restriction at the zoo. This mobile application will greatly help the visitors since most of the visitors feel that it is problematic to find the location of animals. The Taiping Zoo and Night Safari only have a web system with storing information about zoo and the map display is included. The map displays the location of animal and point of interest in zoo. The location of animal in map of Taiping Zoo and Night Safari is not clear and confusing. It is difficult for visitors because might provide inaccurate location for visitors to visiting the animals. In project‟s methodology, five phases in the development of project are involved namely gathering information, application design, application development, testing and evaluation and documentation. All the phases are required to be completed in given period of time. A survey has been conducted before and after development of this application. Additional features and advancement for the application are allowed to be added for future works. The more interactive map and feature being added can make the visitors more enjoying to use the application.